Rapidly Progressed Primary Intestinal Follicular Lymphoma with Elevation of Soluble Interleukin-2 Receptor Levels - Masaya Iwamuro; Ryuta Takenaka; Atsushi Mori; Shigeatsu Fujiki; Takayoshi Miyake; Shoji Asakura; Hiroyuki Okada; Katsuyoshi Takata; Tadashi Yoshino; Kazuhide Yamamoto (Case Reports in Oncological Medicine)
A 62-year-old Japanese male was diagnosed with primary intestinal follicular lymphoma involving the duodenum, jejunum, and rectum without lymph node involvement. The patient was classified as low risk by the follicular lymphoma international prognostic index (FLIPI) system. Treatment was deferred because he had no symptoms. Eleven months after the diagnosis, his soluble interleukin-2 receptor (sIL-2R) levels had risen from 383 to 617 U/mL. Lymphoma progression involving an enlarged perigastric lymph node was also documented. This report illustrates a case of rapidly progressed intestinal follicular lymphoma, suggesting the possible usefulness of sIL-2R levels as an indicator of lymphoma progression.